2011
DOI: 10.1002/j.2050-0416.2011.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanol and Major Volatile Compounds of Turkish Raki and Effect of Distillate Source

Abstract: Turkish Raki is the traditional anise flavoured distillate beverage produced mainly from a grape distillate called suma. Two types of Raki are produced in Turkey according to the distillate source. They are Type I — a fresh grape Raki produced only from suma and Type II — a Raki produced from a blended distillate of suma and alcohol of agricultural origin (mainly molasses). In this study the content of ethanol, methanol, distillate based major volatile compounds (aldehydes, esters, higher alcohols), aniseed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 15 publications
1
40
0
1
Order By: Relevance
“…This may be attributable to the aniseed used for raki production, since the volatile composition of aniseed can change significantly amongst species 9 . Furthermore, in our previous work the aforementioned compounds were not observed, probably due to the direct injection of raki samples, which favours the detection of major volatile compounds 1 . A large part of the volatiles in raki samples are derived from aniseed 9 , except for some fermentative origin esters, such as ethyl octanoate and ethyl decanoate.…”
Section: Label Ethyl Alcohol Content (%) Descriptionmentioning
confidence: 85%
See 2 more Smart Citations
“…This may be attributable to the aniseed used for raki production, since the volatile composition of aniseed can change significantly amongst species 9 . Furthermore, in our previous work the aforementioned compounds were not observed, probably due to the direct injection of raki samples, which favours the detection of major volatile compounds 1 . A large part of the volatiles in raki samples are derived from aniseed 9 , except for some fermentative origin esters, such as ethyl octanoate and ethyl decanoate.…”
Section: Label Ethyl Alcohol Content (%) Descriptionmentioning
confidence: 85%
“…Suma is a distillate containing ca. 94.5% (v/v) alcohol originating from fermented fresh grapes or raisins 1 . Two types of raki are predominantly produced in Turkey, according to the distillate source for the second distillation; the raki produced from only suma and the raki produced from suma and agricultural originated ethyl alcohol 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound is produced in the process of hydrolysis of pectins by specific pectolytic enzymes, and in particular pectin methylesterase [72]. While methanol does not directly affect the flavor of the distillate, it is subjected to restrictive controls owing to its high toxicity [73]. Nevertheless, due to the fact that methanol arises as a result of de-esterification of pectins, which are naturally present in fruits, its presence at limited concentrations in fruit-derived distillates proves the identity of those products [74].…”
Section: Chemical Composition Of the Obtained Distillatesmentioning
confidence: 99%
“…However, when used in Turkish raki, the most resembling spirit to Bogma, HS-SPME revealed the presence of 43 compounds, which were mainly composed of etheric oils from aniseed together with fermentation products (Anli et al, 2007;Yılmaztekin et al, 2011). It is concluded that the main source of volatile compounds are aniseed, fermentation, distillation and maturation (Erten and Canbaş, 2003;Cabaroglu and Yilmaztekin, 2011;Yılmaztekin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%